Analisis Usability pada Aplikasi Akreditasi - Prayudha Wibi Hascarya; Wing Wahyu Winarno; Sudarmawan Sudarmawan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2014)
Currently web accreditation online that is used by BAN-SM DIY is a typical registration system online in enclose menu information of value and a list schools and will in accreditation.According to (Karnohartomo dkk, 2012 ) to develop software interactive, there are two main target for parameters success, namely usability and user experience goals, then the application must be given opportunity for users to complete its activity on the application as well as possible In this research writer using methods PLS (Least Partial Square).According to Tanenhaus dkk, (2010), PLS is a method of analysis which powerful because not based many assumption.Method pls have excellence are data must not normally distributed multivariate (indicators with scales categories, ordinal, intervals until the ratio can be used on the same model) and size samples not necessarily big. Based on the results reliability testing showed that all the items in it 's reliable assessment the questionnaire , with the figures of cronbach alpha & gt; 0.70 and composite reliability & gt; 0.7 .The difference it is evident that the value of cronbachs alpha and composite reliability most are analysis of the path by intervention .Namely relations error with usability correlation value 0,9051 which means that the higher error the higher the relations between variables usability learnability with efficiency namely correlation value of 0,1343 which means that the higher learnability the higher efficiency.